Adaptation and Validation of the Home Numeracy Environment Questionnaire in an Argentine Population (European Journal of Education and Psychology, 2026)
The Home Numeracy Environment (HNE) plays a critical role in children’s early mathematical development. Nevertheless, culturally adapted instruments to assess HNE remain scarce in Latin America, limiting cross-cultural research and local interventions. This study reports the adaptation and validation of the Home Numeracy Environment Questionnaire for the Argentine context. A total of 315 caregivers of children aged 3 to 8 years participated. Reliability analyses showed excellent internal consistency (Cronbach’s α = .89, McDonald’s ω = .92), with item–test correlations above .30. Confirmatory factor analysis (CFA) confirmed a three-factor structure. Factor 1 refers to caregivers’ academic expectations regarding children’s mathematical learning, Factor 2 captures attitudes and beliefs about mathematics, and Factor 3 the frequency of home numeracy activities. Together, these dimensions offer a multidimensional and culturally sensitive perspective on the HNE. Findings support the questionnaire as a psychometrically robust and contextually relevant tool for Argentina. Beyond methodological contributions, the instrument provides a foundation for advancing research on socio-cultural influences in mathematical learning and offers practical guidance for the design of early childhood educational practices and interventions
Keywords: Home Numeracy Environment; Early Mathematical Development; Confirmatory Factor Analysis; Psychometric Validation; Caregiver Beliefs; Early Mathematics; Cultural Adaptation; Child Development